2020
DOI: 10.1016/j.celrep.2020.107979
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid-Mediated GPR35 Signaling in CX3CR1+ Macrophages Regulates Intestinal Homeostasis

Abstract: Highlights d Inflammatory cues and the microbiota modulate Gpr35 expression across species d LPA modulates GPR35-dependent functions in zebrafish and mouse macrophages d GPR35-expressing macrophages have a protective role during intestinal inflammation d GPR35 controls intestinal inflammation by inducing TNF and corticosterone

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 60 publications
0
84
1
Order By: Relevance
“…To characterize the impact of Gpr35 on the epithelial barrier, we made use of the zebrafish ( Dario rerio ) model. Previously, we CRISPR-targeted two GPR35 paralogs in zebrafish, gpr35a and gpr35b , which revealed that the latter is more similar in function to human GPR35 (Kaya et al, 2020). Goblet cell numbers in gpr35b deficient ( gpr35b uu19b2 ) zebrafish were decreased compared to Gpr35 wt larvae (Figures 1A and 1B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To characterize the impact of Gpr35 on the epithelial barrier, we made use of the zebrafish ( Dario rerio ) model. Previously, we CRISPR-targeted two GPR35 paralogs in zebrafish, gpr35a and gpr35b , which revealed that the latter is more similar in function to human GPR35 (Kaya et al, 2020). Goblet cell numbers in gpr35b deficient ( gpr35b uu19b2 ) zebrafish were decreased compared to Gpr35 wt larvae (Figures 1A and 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, susceptibility to C. rodentium increased at an early time point when the innate and not the adaptive immune system is in the process of clearing the infection, further indicating that impaired goblet cells contribute to the increased C. rodentium susceptibility in epithelial Gpr35 -deficient mice. We have previously demonstrated that GPR35 + macrophages show higher transcript levels of pro-inflammatory cytokines, including Il1b and Tnf (Kaya et al, 2020). In turn, these cytokines have been shown to potentiate intestinal permeability (Neurath, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2D, E). CX3CR1 is a maker of residential macrophages in the mucosa 25 . Lack of QKI expression exerted no effect on the typical resident intestinal macrophage (CD45 + CD11b + F4/80 + CX3CR1 + ) population (Fig.…”
Section: Qki Deletion Elevated the Proportion Of M1 Macrophages In Thmentioning
confidence: 99%